The Relationship between Parenting and Family Socioeconomic Status on Adolescent Depression Age 15-17 Years - Burhanto, Burhanto; Safirah, Firda (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Depression in adolescents is usually due to changes that force adolescents to be able to adapt to the changes that occur, several causes of depression in adolescents, one of which is conflict with the family due to factors such as parenting and family socioeconomic status. Objective: Knowing the relationship between Parenting and Family Socioeconomic Status on Depression of Adolescents aged 15-17 years at SMK Kesehatan Samarinda. Method: using quantitative methods with cross sectional design. The sampling technique was Proportionate stratified random sampling with a total of 107 respondents conducted by distributing questionnaires in the form of google forms with test results using the Spearman Rank test. Results: There is a significant relationship between parenting variables and socioeconomic status on adolescent depression at SMK Kesehatan Samarinda with a p value = 0.001 <0.05 on parenting variables, and a p value = 0.000 <0.05 on socioeconomic status variables. Conclusion: there is a significant relationship and sufficient relationship between parenting and family socioeconomic status on adolescent depression aged 15-17 years at SMK Kesehatan Samarinda.